Afganistán: “acción-reacción” en la lucha contra organizaciones violentas extremistas - Lorenzo-Penalva Lucas, José (El Colegio de México A.C., 2023)
This article studies the effects of government actions against insurgency and violent extremist organizations. It is argued that certain state policies and law enforcement actions can have counterproductive effects. Specifically, the “action-reaction” relationship between the surge of foreign troops in Afghanistan and the increase of the number of this force casualties as a result of adverse and counter-reaction in violent extremist jihadist organizations is explored. The findings corroborate and extend other research that suggests that, in certain modern asymmetric conflicts, the more military deployed on the ground, the higher the number of casualties that occur. The study suggests the need for decision-makers in conflicts to ask themselves about the optimal number of people on the ground and to choose courses of action that balance the stated objectives with the risk of troop casualties.